Evidence-Based Strategies for Shortening Informed Consent Forms in Clinical Research. (February 2017) - Corneli, Amy; Namey, Emily; Mueller, Monique P.; Tharaldson, Jenae; Sortijas, Steve; Grey, Thomas; Sugarman, Jeremy
Long informed consent forms (ICFs) remain commonplace, yet they can negatively affect potential participants' understanding of clinical research. We aimed to build consensus among six groups of key stakeholders on advancing the use of shorter ICFs in clinical research. Partnering with the HIV Prevention Trials Network (HPTN), we used a modified Delphi process with semistructured interviews and online surveys. Concerns about redundancy of information were common. Respondents supported three strategies for reducing ICF length: (a) 91% agreed or strongly agreed with grouping study procedures by frequency, (b) 91% were comfortable or very comfortable with placing supplemental information into appendices, and (c) 93% agreed or strongly agreed with listing duplicate side effects only once. Implementing these strategies will facilitate adoption of the proposed changes to U.S. regulations on ICF length, should they be enacted.